HAM, ISLAM DAN KONSTITUSI: MENGKAJI NILAI-NILAI HAK ASASI MANUSIA ISLAM DALAM UUD 1945 - Basuki, Udiyo (Faculty of Law, Tanjungpura University, 2018)
Â The regulation of human rights in the Indonesian constitution, the 1945 Constitution can be interpreted as an effort of citizens to guarantee their protection in the law, so that the constitution can serve as a legal instrument to warn the government not to violate the human rights that have been imposed in the constitution. It is recognized that the protection of human rights is a requirement of the state law, which has been pinned on the Republic of Indonesia. then the protection. Concepts, thoughts and ideas about human rights in Indonesia's constitution have been the pros and cons since the beginning of independence. Certain community groups consider that the human rights contained in the Indonesian constitution are a Western human rights concept that must be rejected because they contain individualistic values and are far from local, religious, especially Islamic values. If more closely scrutinized human rights arrangements in the Indonesian constitution contain Islamic values, characterized by justice, usefulness and public interest; the values contained in the holy book of the Qur'an and the Medina Charter are also recognized as the world's human rights charter. This human rights regulation is closely related to the objectives of Islamic law, namely